Effect of Temperature Increase on Hemoglobin Concentration and Hematocrit Value of Tilapia Fish (Oreochromis niloticus) - Zuhrawati N. A. (Universitas Syiah Kuala, 2014)
This research aims to determine the effect of temperature increase on hemoglobin consentration and hematocrit value of tilapia fish. This research was conducted at Faculty of Veterinary Medicine Syiah Kuala University Banda Aceh. Samples used were blood from tilapia fish thatderived from 12 tilapia fish with weight range of 40-50 g. The research design used was a completely randomized design (CRD) unidirectionalpattern with 3 treatments and 4 replications. P1 as a control group was the treatment with aquarium temperature of 29±1C, P2 was thetreatment with aquarium temperature of 32±1o C, and P3 was the treatment with aquarium temperature of 35±1o C. All aquarium size in thisstudy was 80 cm x 60 cm x 40 cm with the height of water 30 cm. The treatment was carried out for 15 days and on day 16 blood samples werecollected. Blood was taken through the caudalis vein. Data were analyzed by analysis of variance (ANOVA) one way, followed by Tukey test.Mean (± SD) of tilpia fish hemoglobin levels (g/dl) on P1, P2, and P3 were 4.50±0.49, 5.08±0.79, and 6.08±0.94, respectively. Mean (± SD) oftilapia fish hematocrit value (%) in P1, P2, and P3 consecutively were 26.50±8.10, 33.25±11.78, and 40.25±9.04. Statistical analysis showed thatan increase in temperature showed no effect (P 0.05) to the hemoglobin levels of tilapia fish and highly significant to the hematocrit value (P0.01). It can be concluded that the increase of water temperature on 32±1° C and 35±1° C in can increase the hemoglobin levels andhematocrit value of tilapia fish.____________________________________________________________________________________________________________________Key words: tilaphia fish, hemoglobin levels, hematocri value, temperature o